Structure and Mechanical Properties of Al-Cu-Fe-X Alloys with Excellent Thermal Stability - Školáková, Andrea; Novák, Pavel; Mejzlíková, Lucie; Průša, Filip; Salvetr, Pavel; Vojtěch, Dalibor (Materials (Basel, Switzerland), 2017)
In this work, the structure and mechanical properties of innovative Al-Cu-Fe based alloys were studied. We focused on preparation and characterization of rapidly solidified and hot extruded Al-Cu-Fe, Al-Cu-Fe-Ni and Al-Cu-Fe-Cr alloys. The content of transition metals affects mechanical properties and structure. For this reason, microstructure, phase composition, hardness and thermal stability have been investigated in this study. The results showed exceptional thermal stability of these alloys and very good values of mechanical properties. Alloying by chromium ensured the highest thermal stability, while nickel addition refined the structure of the consolidated alloy. High thermal stability of all tested alloys was described in context with the transformation of the quasicrystalline phases to other types of intermetallics.
Keywords: thermal stability; Al-Cu-Fe alloys; quasicrystals; hot extrusion; melt-spinning